La muerte de Tupac Amaro, según las ilustraciones de Guaman Poma de Ayala - Martin Rubio, M. Carmen (2008)
This research analyses the drawings made by the Indian chronicler Felipe Guaman Poma of Ayala in his report called Nueva coronica y Buen Gobierno, on the death of Tupac Amaro, the last monarch of Vilcabamba. The authoress is interested in establishing if these drawings were influenced by Western humanism, the simbolism of the oral Andean tradition or by both